Developed Programs of Research into Corporate Social Responsibility in Relation to Older Adults (the Case of Petroleum Companies); The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 7 : Lifelong Wellbeing in the World (WELLSO 2015) - Goryunova N. N. Nataliya Nikolaevna (2016, 2016)
Title screen